The pivot to online teaching: an opportunity to create effective problem‐based learning environments for dietetic education. - Griffin, Anne (Journal of Human Nutrition & Dietetics, 2025)
Background: Dietetics, as an autonomous profession guided by evidence‐based practice, requires a dynamic and adaptable workforce to meet evolving challenges in healthcare, public health nutrition and epidemiological research. This study aimed to explore the opportunities presented by the transition to online education of preparing dietetic students for professional demands, particularly, through the lens of problem‐based learning (PBL) within the Community of Inquiry (CoI) framework. Methods: This paper examines the shift from traditional classroom and practice placement education to online and blended learning accelerated by the COVID‐19 pandemic. It focuses on the application of PBL, rooted in constructivist theories and the CoI framework, which includes social, cognitive and teaching presences. Results: PBL encourages active and collaborative learning, aligning with the multifaceted roles of dietetic professionals. The CoI framework guides the development of effective online learning environments, emphasising the importance of social, cognitive and teaching presence. Conclusion: The transition to online education presents significant opportunities for dietetic education. Careful instructional design and effective teaching strategies are crucial for creating successful online learning environments, as demonstrated through an illustrative case study. Key points/highlights: The COVID‐19 pandemic accelerated the move towards online and blended learning in dietetics education.The transition to online education demands careful instructional design, planning and development, acknowledging increased time and resource requirements.The Community of Inquiry framework has been proven to be effective in enhancing online learning experiences, particularly, in fostering collaboration and critical thinking among small groups.Strategies for implementing effective online learning experiences using problem‐based learning as a proposed pedagogy are identified for future dietetic teaching and assessment.